The Effect of Health Promotion Support Program on Quality of Life in Patients With Type 2 Diabetes - Fatemeh Zanjani (Qom University of Medical Sciences, 2021)
Background and Objectives: Diabetics need to improve their lifestyle. They should control and prevent the complications of diabetes to improve their quality of life. This study aimed to investigate the effect of health promotion support programs on the quality of life in patients with type 2 diabetes. Methods: The present study was a quasi-clinical trial. A total of 60 people were selected by convenience sampling method and then divided purposefully into intervention (n= 30) and control (n= 30) groups. The health promotion support program was implemented in three stages: review and recognition, support planning, and evaluation. The study data were collected by Demographic and Quality of Life Questionnaire of diabetic patients (DQOL-BCI) before and two months after the intervention in the experimental and control groups. Results: The difference between the two groups regarding gender, age, marriage, education, and the job was not significant. The Mean±SD score of quality of life in the intervention group before the intervention was 46.8±8.06 and increased after the intervention to 56.8±6.06 (P <0.001). The Mean±SD score of quality of life in the control group before the intervention was 46.9±6.7 and increased after the intervention to 49.7±5.6, and this difference was statistically significant (P<0.001). The increase in the quality of life score of the intervention group was 10 units, but it was 2.87 units in the control group. Before the intervention, the difference in the quality of life scores of the two groups was not significant (the independent t-test, P=0.98), but after the intervention, this difference was significant (the independent t-test, P<0.001). Conclusion: The results showed that implementing a health promotion support program effectively improved the quality of life of type 2 diabetic patients. Therefore, it is suggested to be used as an effective method in improving the quality of life of diabetic patients and other chronic diseases.